3′,6′-Bis(diethylamino)-3H-spiro[2-benzothiophene-1,9′-xanthene]-3-thione - Su, Bing-Yuan (International Union of Crystallography, 2008)
The title compound, C(28)H(30)N(2)OS(2), was obtained by thionation of 3′,6′-bis(diethylamino)-3H-spiro[isobenzofuran-1,9′-xanthene]-3-one with 2,4-bis(p-methoxyphenyl)-1,3-dithiadiphosphetane disulfide (Lawesson’s reagent). The planes of the two benzene rings of the xanthene system are inclined at a dihedral angle of 17.4 (1)°, and the plane of the dithiophthalide group and the planes through the two benzene rings of the xanthene system make dihedral angles of 80.2 (1) and 82.8 (1)°, respectively.